Answer:
[tex]y=\sqrt{x}+5[/tex]
Step-by-step explanation:
The inverse of a function, is the function or rule formed by reflecting the line over y=x. This means essentially that all (x,y) values from the original function switch to (y,x).
(x,y)--->(y,x) in the new function.
If the function has points (-3,4) and (5,-2) then the inverse has points (4,-3) and (-2, 5).
We can find the equation of the inverse by switching x and y in the equation and solving for y.
This means that [tex]y=(x-5)^2[/tex] becomes [tex]x=(y-5)^2[/tex]. We now solve for y through inverse operations.
[tex]x=(y-5)^2[/tex]
[tex]x=(y-5)^2\\\sqrt{x} =\sqrt{(y-5)^2} \\\sqrt{x} =y-5\\\sqrt{x} +5=y[/tex]